Mechanism of the rice hull‐induced germination of Monochoria vaginalis seeds in darkness - Yokota, Takao; Handa, Hiromi; Yamada, Yumiko; Yoneyama, Koichi; Takeuchi, Yasutomo (Weed biology and management, 2014)
The seeds of Monochoria vaginalis require light to germinate. However, they are able to germinate in darkness in the presence of rice hulls. The mechanism of this phenomenon was investigated in this study, in which only the unsterilized seeds of Monochoria were induced to germinate by the presence of a rice hull extract. The rice hull extract was able to be replaced by either a mixture of amino acids and phosphate or a yeast extract. The culture media in which germination was observed always showed turbidity, indicating the propagation of bacteria, which were identified as Bacillus sp., Pedobacter sp., Pantoea sp. and Sphingomonas sp. Treatment with the individual bacterial species or combinations of these bacteria induced Monochoria seed germination when added to the media containing the rice hull extract. It was concluded that the rice hull extract accelerates the propagation of bacteria, which in turn digest the seed coat of Monochoria, facilitating its germination.